Tax Strategy Disclosure: A Greenwashing Mandate - Katarzyna A. Bilicka; Elisa Casi; Carol Seregni; Barbara Stage (Center for Economic Studies and Ifo Institute (CESifo), 2022)
Firms constantly face new and more stringent tax disclosure requirements and, increasingly, paying a fair share of tax is seen as part of corporate social responsibility. In this paper, we investigate whether mandating qualitative tax disclosure leads to intended outcomes, using, as an exogenous shock, the 2016 UK reform that required the disclosure of tax strategy for firms above a certain size threshold. The goal of the mandate was to increase the availability of tax information to the general public and to decrease tax avoidance. We find that treated firms - those that are required to publish a tax strategy report- significantly increase the volume, but not the quality, of tax strategy disclosure in the annual reports. We show an important role that public pressure plays in facilitating this increase in disclosure volume even in the absence of the mandate. We document no significant effect on tax avoidance. Our findings indicate that a qualitative tax disclosure requirement has incentivized firms to portray themselves as "good tax citizen", resulting in lengthier but unsubstantiated disclosures in the annual reports without affecting their tax avoidance practices.
Keywords: G38; M41; M48; H26; H20; 330; Disclosure Regulation; Nonfinancial Disclosure; Corporate Social Responsibility; Tax Transparency; Corporate Avoidance